BIOLOGICAL CHARACTERISTICS OF SPOTTED SCAT SCATOPHAGUS ARGUS (LINNAEUS) IN BINH DAI DISTRICT, BEN TRE PROVINCE - Linh, Vo Dinh; Mao, Nguyen Dinh (Vietnam Journal of Marine Science and Technology, 2008)
Within the period of July, 2005 to June, 2006, a total of 373 spotted scats were obtained. Total length in mm,  body weight and gonad weight in grams were studied. The total length at maximum size was 281 mm (♀). The length - weight relationship was determined following for female W♀ = 10-1L-2.8384, for male W♂ = 10-1L2.8384. Food compositions of spotted scat were mainly Scatophagus,  Phytoplankton and some Zooplankton. Spawning occurred year-round with peak activity from August to  October. Size at maturity was 100 mm (Lt) for female.